Zbiorowe pisanie biografii jako metoda uczenia się o sobie, o innych, o świecie - Zbróg, Zuzanna (Studia Edukacyjne, 2020)
The article presents an example of poststructuralist interpretation of biography episode written by students on the topic: “Becoming someone”. The poststructuralist analysis focuses on the perception of the subject-in-process, requires destabilization ofrational stable andunifiedconcepts.It aims at researching the functions and results of regularities of a process in case of author’s own research – the process of becoming a teacher in classes I-III. People engaged in CBW have a chance to understand their own situation by trying to answer the questions concerning what we really know about ourselves and the reality. The article discusses chosen theoretical assumptions and elements of the methodological procedure applied in the method of collective biography writing. The article is closed with remarks for the work with students which were verifiedin practice. This may help other researchers when they start working with this method.